PENDAMPINGAN PERIKANAN TERPADU SERTA PAKAN MANDIRI DI DESA BUNUTIN, KECAMATAN BANGLI, KABUPATEN BANGLI - I Made Tamba; Nyoman Yudiarini; Ida Ayu Made Dwi Susanti; Yosefiano Rigeri Rovinus Parowa; Gonsaga F Jesen; Ni Made Martini Ariesti (Jurnal Abdi Insani, 2026)
The program in Bunutin Village, Bangli District, was implemented to improve the efficiency of fish farming while reducing farmers’ dependence on commercial feed through the application of integrated aquaculture and independent feed production. The main issues faced by the community include limited knowledge, skills, and experience in practicing sustainable aquaculture, as well as the lack of access to alternative feed sources that are cheaper, environmentally friendly, and easy to produce independently. To address these challenges, the program introduced the use of African Nightcrawler earthworms (Eudrilus eugeniae) as a high-protein feed source. The activities were carried out over ten months, covering preparation, technical training, mentoring, and evaluation stages. The training provided comprehensive guidance on earthworm cultivation, media management, humidity and temperature control, and integration with aquaculture systems. Participants were also taught how to utilize organic waste as earthworm culture media and to use worms as live feed or feed meal, while also producing vermicompost for crops. Evaluations through pre-test and post-test showed significant improvements: understanding of feed production increased from 46.6% (less interested) to 71.8% (highly interested), and practical skills improved from 40.5% (poor) to 77.5% (very good). The program outputs included media publications, journal articles, training videos, and enhanced farmer capacity. The program proved effective in promoting feed self-sufficiency and establishing an environmentally friendly bio-circular system. Subsequent steps focus on technology replication, development of processed feed such as pellets, and strengthening farmer institutions to ensure sustainability and wider adoption. This model is suitable for rural areas as a cost-effective and eco-friendly solution for integrated agriculture and aquaculture. This program enhances feed self-sufficiency, strengthens farmers’ capacity, and develops a sustainable bio-circular system that effectively supports integrated agriculture–aquaculture in Bunutin Village.